THE EFFECT OF WORK-LIFE BALANCE ON JOB SATISFACTION: LITERATURE REVIEW - zahara meutia; putri mauliza (Institute of Computer Science (IOCS), 2022)
Concept of work has been changed, work from the office to work from home and now into a hybrid working combination of work from home and work from office is the result of the COVID-19 pandemic which drastically changed work trends. LinkedIn talent drivers survey June 2021 reported most priorities for an employee are work-life balance, compensation and benefits, colleagues and culture. Work-life balance was already the overall first priority for employees at the beginning of the pandemic and it’s only grown more important as remote work becomes more common. This study aims to conduct a scientific study of the role of work-life balance on job satisfaction. The method in this study is a literature study based on previous research with criteria that are in accordance with the research variables which is work-life balance on job satisfaction. Company participations to create work-life balance is subtanstial. The company must know to see how importance work-life balance for their employee and be able to fulfill needs of employees explicitly or implicitly Flexible working hours are important for employees. Being able to divide time between work life and personal life so they can be productive at work and feel job satisfactionin and employee loyalty created. Keywords: Work-Life Balance, Job Satisfaction